2007
DOI: 10.3748/wjg.v13.i15.2240
|View full text |Cite
|
Sign up to set email alerts
|

Complicated small-bowel diverticulosis: A case report and review of the literature

Abstract: While jejunoileal diverticula are rare and often asymptomatic, they may lead to chronic non-specific or acute symptoms. The large majority of complications present with an acute abdomen similar to appendicitis, cholecystitis or colonic diverticulitis but they also may appear with atypical symptoms. As a result, diagnosis of complicated jejunoileal diverticulosis can be quite difficult, and may solely depend on the result of surgical exploration. In the absence of contra-indications, diagnostic laparoscopy has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
135
0
14

Year Published

2009
2009
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 103 publications
(151 citation statements)
references
References 11 publications
2
135
0
14
Order By: Relevance
“…Also to add, these histological fi ndings are consistent with GI motility disorders like progressive systemic sclerosis, visceral myopathy and visceral neuropathies [7]. In fact, JD can be seen in elderly people with peristaltic disorders, such as progressive systemic sclerosis, leading to intestinal obstruction which in turn causes retention of faeces or gas in distal bowel, producing increased intraluminal pressure [4,7]. Increased intraluminal pressure acts at the weakest points in the muscle layers of jejunum i.e.…”
Section: Discussionsupporting
confidence: 57%
See 3 more Smart Citations
“…Also to add, these histological fi ndings are consistent with GI motility disorders like progressive systemic sclerosis, visceral myopathy and visceral neuropathies [7]. In fact, JD can be seen in elderly people with peristaltic disorders, such as progressive systemic sclerosis, leading to intestinal obstruction which in turn causes retention of faeces or gas in distal bowel, producing increased intraluminal pressure [4,7]. Increased intraluminal pressure acts at the weakest points in the muscle layers of jejunum i.e.…”
Section: Discussionsupporting
confidence: 57%
“…Microscopic examinations of JD specimens have shown that fi brosis along with degeneration or decrease in number of normal muscle cells, or, de- generation of neurons occurring in intestinal wall underlies these dysfunctions. Also to add, these histological fi ndings are consistent with GI motility disorders like progressive systemic sclerosis, visceral myopathy and visceral neuropathies [7]. In fact, JD can be seen in elderly people with peristaltic disorders, such as progressive systemic sclerosis, leading to intestinal obstruction which in turn causes retention of faeces or gas in distal bowel, producing increased intraluminal pressure [4,7].…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…4,5 This explains their typical location at the mesenteric side. 1,4,6 Diverticula are more frequent in jejunum (61%) than the other parts of the small bowel and it is attributed to the greater diameter of the penetrating jejunal artery. 5 Coexistent diverticuli are found in many other digestive localization.…”
Section: Discussionmentioning
confidence: 99%